ความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง - ด้วงติลี, พนัด (วารสาร ศึกษาศาสตร์ มมร; Vol 7 No 2 (2019): วารสารศึกษาศาสตร์ มมร ปีที่ 7 ฉบับที่ 2 (กรกฎาคม - ธันวาคม 2562), 2020)
การวิจัยครั้งนี้มีวัตถุประสงค์ คือ 1) เพื่อศึกษาความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง 2) เพื่อศึกษาปัจจัยที่มีผลต่อความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง 3) เพื่อศึกษาเปรียบเทียบความเป็นพลเมืองของนักเรียนโรงเรียนสังกัดหน่วยงานรัฐกับหน่วยงานคณะสงฆ์ 4) เพื่อศึกษาปัญหาและอุปสรรคของความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง การวิจัยครั้งนี้ใช้วิธีการผสมผสานระหว่างการวิจัยเชิงคุณภาพและการวิจัยเชิงปริมาณ ประชากรและกลุ่มตัวอย่างมี 2 ประเภท คือ 1) ประชากรและกลุ่มตัวอย่างสำหรับการวิจัยเชิงคุณภาพ คือ ผู้บริหารกระทรวงศึกษาธิการ จำนวน 2 ท่าน และครู จำนวน 12 ท่าน ประชากรและกลุ่มตัวอย่างสำหรับการวิจัยเชิงปริมาณ คือ นักเรียน 4 โรงเรียน จำนวน 3,892 คน ใช้ตารางกำหนดขนาดกลุ่มตัวอย่างของเครจซี่และมอร์แกน ได้กลุ่มตัวอย่าง จำนวน 351 คน และใช้วิธีการสุ่มอย่างง่าย  เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบสัมภาษณ์และแบบสอบถาม การวิเคราะห์ข้อมูลเชิงคุณภาพใช้วิธีวิเคราะห์เนื้อหา การวิเคราะห์ข้อมูลเชิงปริมาณใช้สถิติเชิงพรรณนา คือ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ข้อค้นพบของการวิจัยมีดังต่อไปนี้ คือ ความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง พบว่า 1) ความร่วมมือในระดับนโยบาย พบว่า มีหลายนโยบายที่เสริมสร้างการศึกษาเพื่อความเป็นพลเมือง เช่น นโยบายด้านศาสนา และนโยบายด้านการศึกษาของคณะสงฆ์ เป็นต้น ส่วนยุทธศาสตร์การสร้างความร่วมมือ ได้แก่ การก่อตัวนโยบาย การกำหนดนโยบาย การตัดสินเลือกนโยบาย การนำนโยบายไปปฏิบัติ และการประเมินผลนโยบาย 2) ความร่วมมือในระดับปฏิบัติการ พบว่า มีหลายหน่วยงาน            ที่ให้ความร่วมมือในการจัดการศึกษาเพื่อความเป็นพลเมือง ส่วนยุทธศาสตร์สร้างความร่วมมือ ได้แก่  การตระหนักและรับรู้ปัญหา การวางแผน การปฏิบัติตามแผนและการประเมินผลการปฏิบัติตามแผน ปัจจัยที่มีผลต่อความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง พบว่า 1) หลักสูตรการศึกษา มีเนื้อหาเกี่ยวกับความเป็นพลเมืองชัดเจนทั้งในระดับประถมศึกษา และระดับมัธยมศึกษา 2) หนังสือแบบเรียน มีเนื้อหาเกี่ยวกับความเป็นพลเมืองครบ ทุกระดับชั้น 3) การจัดกิจกรรมการเรียนรู้ที่เสริมสร้างความเป็นพลเมืองมี 2 ประเภท ได้แก่ กิจกรรมการเรียนรู้ในชั้นเรียน และกิจกรรมการเรียนรู้นอกชั้นเรียน 4) ครูมีปัญหาหลายอย่าง เช่น จำนวนมีน้อย ขาดความรู้เรื่องพลเมือง และไม่ได้รับการสนับสนุนจากผู้บริหาร เป็นต้น นักเรียนโรงเรียนที่สังกัดหน่วยงานของคณะสงฆ์มีความเป็นพลเมืองมากกว่านักเรียนโรงเรียนที่สังกัดหน่วยงานของรัฐ เนื่องจากหลายปัจจัย เช่น 1)โครงสร้าง การบริหารและสภาพแวดล้อม 2) หลักสูตรการศึกษา 3) การจัดกิจกรรมการเรียนรู้ 4) สถานภาพของครู 5) สถานภาพของผู้เรียน เป็นต้น 4. ปัญหาอุปสรรคของความร่วมมือระหว่างรัฐกับคณะสงฆ์ในการเสริมสร้างการศึกษาเพื่อความเป็นพลเมือง ได้แก่ 1) ผู้บริหารไม่เข้าใจการจัดการศึกษาเพื่อความเป็นพลเมือง 2) ขาดเจ้าภาพหลักในการดำเนินการ 3) ขาดการกำหนดนโยบายและแผนงานร่วมกัน 4) ขาดแคลนทรัพยากรที่จำเป็น 5) ขาดการประสานงานที่ดี ส่วนแนวทางแก้ไขปัญหา ได้แก่ 1) รัฐบาลต้องประสานงานกับคณะสงฆ์ทั้งที่เป็นทางการและไม่เป็นทางการ 2) ร่วมมือกันจัดตั้งศูนย์การศึกษาเพื่อความเป็นพลเมือง 3) ร่วมมือกันกำหนดเป็นนโยบาย 4) ประชุมสัมมนาผู้บริหารและผู้ที่เกี่ยวกับข้องอย่างต่อเนื่อง   The purposes of this research  were 1) to study the collaboration  of  Thai state and Sangha in strengthening civic education. 2) to study factors affecting to the collaboration of Thai state and Sangha in strengthening  civic education. 3) to study compare citizenship of school students under government  organization and Sangha organization. 4) to study problems and obstacles of collaboration of Thai state and Sangha in strengthening  civic education. This research mixed between qualitative research and quantitative research. There are 2 types of population and sample groups. 1) Population and sample group for qualitative research were 2 executives from the Ministry of Education and 12 teachers. Population and sample group for quantitative research were 3,892 students in 4 schools. Use the sample size table of Krececie and Morgan. Get a sample of 351 people and use simple random methods. Tools used in data collection were interview forms and questionnaires. Qualitative data analysis using content analysis method. Quantitative data analysis using descriptive statistics was percentage, mean and standard deviation.The findings of the research were as follows : 1. Level of  the collaboration  of  Thai state and Sangha in strengthening civic education found that (1) collaboration at the policy level found that there are many policies that enhance education for citizenship such as religious policies And the educational policy of the clergy, etc. The collaboration strategies were policy formation, policy formulation, judging policy choices, implementing policies and policy evaluation. (2) collaboration at the operational level found that there were many organizations to collaborate in strengthening civic education such as the Prime Minister's Office, Office of the Education Council, Ministry of Education, Religious department Ministry of Culture, National Buddhism Office, Schools and Temples, etc. The collaboration strategies were awareness and recognize the problem, planing, to follow the plan, and evaluation of plan implementation.2. Factors affecting to the collaboration of Thai state and Sangha in strengthening  civic education found that : 1) Curriculum  has clear content about citizenship both at the primary school level, lower and upper secondary school level. 2) Textbook has content about citizenship at all levels But cannot enhance citizenship. 3) There are 2 types of learning activities that enhance citizenship. They were Including classroom learning activities and learning activities outside the classroom. 4) The role of teachers found that teachers now face many problems such as the number is low, lack of knowledge about citizens And not being supported by executives. 3. Students in schools that are affiliated with the Sangha units have citizenship more than students in schools that are under the government unit. Which is caused by many factors such as 1) management structure And environment 2) education program 3) learning activity management 4) teacher status 5) student status and 6) living in and outside of the school's students etc. Problems, obstacles and guidelines for solving inter-state cooperation with the Sangha in enhancing education for citizenship, including 1) Executives do not understand the management of education for citizenship 2) There are no main hosts in the operation 3) No policy and plan together As for the solution, the problems are as follows: 1) The government must coordinate with both formal and informal clergy 2) Collaborate to set up the Center for Citizenship Education 3) Collaborate to formulate policies 4) Seminars for executives and those who About continuous involvement